Stabilization of Wind Generator by Using STATCOM/SMES (Journal of Scientific Research, 2009)
In this work, the STATCOM/SMES system with a voltage-source IGBT converter is modeled as a controllable energy source. The objective of the proposed STATCOM/SMES topology is to provide both active and reactive power, which can significantly decrease the voltage and power fluctuations of grid connected fixed speed wind generators. One major problem in wind generator output power smoothing is setting of the reference output power. Constant output power reference is not a good choice because there can be some cases where wind speed is very low and then sufficient power cannot be obtained. In that case, energy storage device can solve the problem but large energy capacity may be needed. To generate output power reference, a Simple Moving Average (SMA) technique is used which corresponds to the energy storage capacity. Thus the capacity of SMES can be small (50% of wind farm capacity). Real wind speed data is used in the simulation analyses, which validates the effectiveness of the proposed control strategy. Keywords: STATCOM/SMES; Energy storage system (ESS); Simple moving average (SMA); Fixed speed wind generator; Voltage source converter (VSC).© 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i3.2605         J. Sci. Res. 1 (3), 528-538 (2009)